The E3 ligase tripartite motif 8 targets TAK1 to promote insulin resistance and steatohepatitis. Issue 5 (22nd March 2017) - Yan, Feng‐Juan; Zhang, Xiao‐Jing; Wang, Wen‐Xin; Ji, Yan‐Xiao; Wang, Pi‐Xiao; Yang, Yang; Gong, Jun; Shen, Li‐Jun; Zhu, Xue‐Yong; Huang, Zan; Li, Hongliang
Abstract : Tripartite motif 8 (TRIM8), an E3 ligase ubiquitously expressed in various cells, is closely involved in innate immunity. However, its role in nonalcoholic steatohepatitis is largely unknown. Here, we report evidence that TRIM8 is a robust enhancer of steatohepatitis and its complications induced by a high‐fat diet or a genetic deficiency ( ob/ob ). Using gain‐of‐function and loss‐of‐function approaches, we observed dramatic exacerbation of insulin resistance, hepatic steatosis, inflammation, and fibrosis by hepatocyte‐specific TRIM8 overexpression, whereas deletion or down‐regulation of TRIM8 in hepatocytes led to a completely opposite phenotype. Furthermore, investigations of the underlying mechanisms revealed that TRIM8 directly binds to and ubiquitinates transforming growth factor‐beta–activated kinase 1, thus promoting its phosphorylation and the activation of downstream c‐Jun N‐terminal kinase/p38 and nuclear factor κB signaling. Importantly, the participation of TRIM8 in human nonalcoholic fatty liver disease and nonalcoholic steatohepatitis was verified on the basis of its dramatically increased expression in the livers of these patients, suggesting a promising development of TRIM8 disturbance for the treatment of nonalcoholic steatohepatitis–related metabolic disorders. Conclusion : The E3 ligase TRIM8 is a potent regulator that exacerbates steatohepatitis and metabolic disorders dependent on its binding and ubiquitinating capacity on transforming growth factor‐beta–activated kinase 1. (Hepatology 2017;65:1492‐1511)